CHARACTERISTIC OF MAMMOGRAPHY COMPARED WITH HISTOPATHOLOGY RESULT AT RSUP DR. KARIADI - Molly Inta Sari; RR Lydia Purna Widyastuti Setjadiningrat Kuntjoro; Edmond Rukmana Wikanta; Sukma Imawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
AbstractBackground: Breast tumors are common lesions found in women.[1] Mammography is Food and Drugs Administration (FDA) approved modality for screening and diagnosing breast tumor.[2,3] Aim: To know the characteristic and comparison of mammography results with histopathology diagnosis as the gold standard in breast tumor patients at RSUP Dr. Kariadi. Methods: This research used the diagnostic test method. Data were taken from medical records in RSUP Dr. Kariadi, Semarang from 2017 to 2019 with sa consecutive sampling method. The collected samples were 55 mammography imaging. Next, the data were described as frequency distribution and percentages, and then the diagnostic test values were counted. Result: Benign breast tumor in RSUP Dr. Kariadi was found in 40-50 years old patients with 77,8% oval-shaped and 72,2% circumscribed margin mass seen in the mammogram, while breast cancer was found in >50 years old patients with 57,1% irregular-shaped and 54,3 spiculated margin mass seen in the mammogram. Mammography in RSUP Dr. Kariadi has 89% sensitivity, 89% specificity, 94% positive predictive value, 81% negative predictive value, and 89% accuracy. Conclusion: Benign breast tumor in RSUP Dr. Kariadi mostly found in 40-50 years old patients with oval-shaped and circumscribed margin mass seen in the mammogram, while breast cancer is mostly found in >50 years old patient with irregular shape and spiculated margin mass seen in the mammogram. The diagnostic test score of mammography in RSUP Dr. Kariadi is high.